1997
DOI: 10.1101/lm.4.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Intact enhancement of declarative memory for emotional material in amnesia.

Abstract: Emotional arousal has been demonstrated to enhance declarative memory (conscious recollection) in humans in both naturalistic and experimental studies. Here, we examined this effect in amnesia. Amnesic patients and controls viewed a slide presentation while listening to an accompanying emotionally arousing story. In both groups, recognition memory was enhanced for the emotionally arousing story elements. The magnitude of the enhancement was proportional for both amnesic patients and controls. Emotional reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 30 publications
5
56
0
3
Order By: Relevance
“…For instance, several studies indicate that the amygdala has anatomical and neurochemical properties making it particularly suitable to modulate higher cognitive functions (Emery and Amaral, 2000;Davis and Whalen, 2001;Ghashghaei and Barbas, 2002). In addition, numerous studies have found evidence that the amygdala modulates cognition in the case of the emotional enhancement of long-term memory (Hamann et al, 1997(Hamann et al, , 1999Philippot and Schaefer, 2001;Smith et al, 2005Smith et al, , 2006LaBar and Cabeza, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several studies indicate that the amygdala has anatomical and neurochemical properties making it particularly suitable to modulate higher cognitive functions (Emery and Amaral, 2000;Davis and Whalen, 2001;Ghashghaei and Barbas, 2002). In addition, numerous studies have found evidence that the amygdala modulates cognition in the case of the emotional enhancement of long-term memory (Hamann et al, 1997(Hamann et al, , 1999Philippot and Schaefer, 2001;Smith et al, 2005Smith et al, , 2006LaBar and Cabeza, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest that amygdala damage eliminates the facilitatory effect of arousal, but does not alter the effect of emotional valence (Phelps et al, 1998). In fact, there is a double dissociation between the effects of hippocampal and amygdaloid damage: medial-temporal amnesics still show enhanced recall for emotional stimuli (Hamann et al, 1997), but amygdala patients do not differ from healthy controls on recall of nonemotional stimuli (Adolphs et al, 1997). Finally, although the amygdala plays a role in the encoding of emotional stimuli, little is known of its role during retrieval; one study reports left amygdala activation during the retrieval of emotional memories (Dolan et al, 2000), while another reports right amygdala activity during autobiographical memory retrieval in general (Fink et al, 1996).…”
Section: Neuropsychological Datamentioning
confidence: 99%
“…GABA agonists infused directly into the amygdala immediately after training impaired retention (Castellano et al 1989;Willensky et al 2000). Amygdala is reported to play a crucial role, preferentially in avoidance learning than spatial learning (Takashina et al 1995) and is also involved with the formation of enhanced declarative memory for emotionally arousing events (Adolphs et al 1997;Cahill and McGaugh 1998;Hamann et al 1997). Declarative memory also depends on signals from the hippocampus and other parts of the medial temporal lobe of the brain for its retention.…”
Section: Memory Retention and Cognitionmentioning
confidence: 99%